2020
DOI: 10.1021/acs.iecr.0c03415
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotubes: An Advanced Electron Transport Material for Enhancing the Efficiency and Stability of Perovskite Solar Cells

Abstract: Despite the preferential use of titanium dioxide (TiO2) as electron transport layers (ETLs) for perovskite solar cells (PSCs), some problems are still needed to be solved to achieve better power conversion efficiency (PCE). Herein, TiO2 nanotubes (TD-NTs) with network structures have been obtained through an inexpensive hydrothermal strategy. The obtained TD-NTs have been used in constructing PSCs as a favorable interface ETL. The PSC based on TD-NTs displayed a high PCE of 19.14%, increased by 11.4% compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…The common materials exploited as electron transport layer in regular configuration are generally n-type semiconductor metal oxides such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), tin dioxide (SnO 2 ), whereas fullerene derivatives such as C 60 and phenyl-C 61 -butyric acid methyl ester (PCBM) are preferred in inverted configuration. Otherwise, the familiar materials involved 2,2′,7,7′-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD), poly (3,4-ethylenedioxythiophene): poly(styrene-sulfonate) (PEDOT:PSS), poly [bis(4-phenyl)(2,4,6-trimethylphenyl) amine] (PTAA), nickel oxide (NiO x ), copper (I) iodide (CuI), copper iron oxide (CuFeO 2 ), copper chromium oxide (CuCrO 2 ), and copper thiocyanate (CuSCN) are ordinarily applied as an hole transport layer in perovskite solar cells architecture (Rashad and Shalan 2014;Elseman et al 2020Elseman et al , 2019Atabaev 2017;Olivera et al 2018;Akin et al 2019b, a;Akin et al 2018;Mudhoo et al 2020;Sengul and Asmatulu 2020;Shukla and Oturan 2015;Mohammed et al 2020). Both electron transport layer and hole transport layer are responsible for obtaining effective solar cells as the perovskite layer can absorb the light to separate the charges, the electron transfer to electron transport layer and the hole transfer to hole transport layer and when the layers work efficiently, the amount of charge separation increases and the recombination process between carriers decreases.…”
Section: Introductionmentioning
confidence: 99%
“…The common materials exploited as electron transport layer in regular configuration are generally n-type semiconductor metal oxides such as titanium dioxide (TiO 2 ), zinc oxide (ZnO), tin dioxide (SnO 2 ), whereas fullerene derivatives such as C 60 and phenyl-C 61 -butyric acid methyl ester (PCBM) are preferred in inverted configuration. Otherwise, the familiar materials involved 2,2′,7,7′-Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD), poly (3,4-ethylenedioxythiophene): poly(styrene-sulfonate) (PEDOT:PSS), poly [bis(4-phenyl)(2,4,6-trimethylphenyl) amine] (PTAA), nickel oxide (NiO x ), copper (I) iodide (CuI), copper iron oxide (CuFeO 2 ), copper chromium oxide (CuCrO 2 ), and copper thiocyanate (CuSCN) are ordinarily applied as an hole transport layer in perovskite solar cells architecture (Rashad and Shalan 2014;Elseman et al 2020Elseman et al , 2019Atabaev 2017;Olivera et al 2018;Akin et al 2019b, a;Akin et al 2018;Mudhoo et al 2020;Sengul and Asmatulu 2020;Shukla and Oturan 2015;Mohammed et al 2020). Both electron transport layer and hole transport layer are responsible for obtaining effective solar cells as the perovskite layer can absorb the light to separate the charges, the electron transfer to electron transport layer and the hole transfer to hole transport layer and when the layers work efficiently, the amount of charge separation increases and the recombination process between carriers decreases.…”
Section: Introductionmentioning
confidence: 99%
“…In the two-step method, PbI 2 is dissolved in the solvent (DMF) and spin-coated onto the substrate. Then, CH 3 NH 3 I is dissolved in the solvent (isopropanol (IPA)) and spin-coated onto the PbI 2 -coated substrate [7,53].…”
Section: Device Fabrication Methodsmentioning
confidence: 99%
“…Therefore, some researchers have resorted to using TiO2 nanotube (TD-NT) as an electron transport layer. Under the same conditions, they found that PSC based on TD-NT has a higher PCE (19.14%) compared to PSC that used TiO2 nanoparticles (TD-NP) (17.18%) [67]. It was somehow essential to manage photons to realize Perovskite-Si tandem solar cells with power conversion efficiencies that jump over the records of single-junction solar cells.…”
Section: Evolution Of Perovskite-based Tandem Solar Cellsmentioning
confidence: 99%